Non-Hodgkin’s Lymphoma Presenting as Intracardiac Mass : A Rare Presentation - Caryn Tsujean, Lim; Ho, Yik Hon; Ling, Hwei Sung; Chung, Bui Khiong; Grace Lee, Wan Chieng; Leong, Tze Shin; Oon, Yen Yee; Chew, Lee Ping (Asian Society of Cardiovascular Imaging, 2023)
Primary cardiac lymphoma (PCL) comprises of 1%–2% of primary cardiac tumors. This case report describes a rare case of PCL with rapid disease progression. A 51-year-old female presented with 6 months of dyspnea. Her transthoracic echocardiogram showed a large exudative circumferential pericardial effusion and bi-atrial masses. An endovascular tissue biopsy using intra-cardiac echocardiography guidance enabled the diagnosis of diffuse large B-cell lymphoma. Staging computed tomography staged the disease at Ann Arbor stage IV E. She achieved a complete response to rituximab, cyclophosphamide, hydroxydaunorubicin, vincristine, and prednisolone chemoimmunotherapy.